The EU and law in context: the context - Carol Harlow (European Law Open, 2022)
It is widely acknowledged that the contextual study of European Community law, later European Union law, has contributed to a richer understanding of EC/EU law. This review proposes a contextual reconstruction and analysis of EC/EU law in context, or what is the same, it considers the institutions, milieus and debates which fostered the analysis and assessment of EC and EU law as ‘an intricate web of politics, economics and law’, at the same time that facilitated the development of critical self-consciousness about the underlying assumptions that scholars (including contextual scholars) bring to their study of law. This is done by engaging with the work of Francis Snyder, and in particular, with his groundbreaking collection “New Directions in European Community law”.